Defining the clinical outcome status (COS) in sarcoidosis: results of WASOG Task Force - Baughman, R.P.; Nagai, S.; Balter, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
The clinical outcome of sarcoidosis is quite variable. Several scoring systems have been used to assess the level of disease and clinical outcome. The definition of clinical phenotypes has become an important goal as genetic studies have identified distinct genotypes associated with different clinical phenotypes. In addition, treatment strategies have been developed for patients with resolving versus non resolving disease. A task force was established by the World Association of Sarcoidosis and Other Granulomatous diseases (WASOG) to define clinical phenotypes of the disease based on the clinical outcome status (COS). The committee chose to examine patients five years after diagnosis to determine the COS. Several features of the disease were incorporated into the final nine categories of the disease. These included the current or past need for systemic therapy, the resolution of the disease, and current status of the condition. Sarcoidosis patients who were African American or older were likely to have a higher COS, indicating more chronic disease. The COS may be useful in future studies of sarcoidosis.